Analisis Tindak Tutur Pragmatik dalam Cerpen “Batu di Pekarangan Ruma Karya Sapardi Djoko Damono - Tiwi Widya Lestari; Iktarna Faris Saufaqillah; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Literary works are a medium to convey messages and values of life through unique language. One form of literary work is a short story that can be studied through a pragmatic approach. This study aims to examine the types of speech acts in the short story Batu di Pekarangan Rumah by Sapardi Djoko Damono. The research method used is descriptive qualitative method. The data were obtained through reading and recording techniques, then analyzed based on the classification of speech acts, namely question, statement, and expressive speech acts. The results show that the main character's speech in this short story contains many questioning and expressive speech acts that reflect the emotional closeness between the character “I” and the stone that is the object of his childhood memories. The speech acts not only show the function of communication, but also imply a deep meaning of loneliness, loss, and nostalgia. This research is expected to contribute to the study of pragmatics in the analysis of literary works, especially short stories.